The Diagnostic Value of Serum Leucine Aminopeptidase - Miller, Morris C. (1963)
Experience with serum leucine aminopeptidase determination in 61 patients led to the following conclusions. The test is no more sensitive than the alkaline phosphatase test in cases of carcinoma of the pancreas. It is elevated in all cases of obstructive and hepatogenous jaundice and serves no useful function in their differentiation. It was a valuable test in cases of calculous biliary tract disease, being more sensitive than either bilirubin or alkaline phosphatase determinations. In three instances of elevated leucine aminopeptidase in disorders apparently not related to the liver or pancreas, laparotomy and autopsy showed involvement of these organs in two.